PERMUKIMAN KUMUH, MASALAH ATAU SOLUSI? - Putu Sueca, Ngakan (Jurnal Natah; Vol. 2, No. 2 Agustus 2004, 2012)
A house perhaps is a dream for everybody. Whatever the condition, one’s live mostly is started, enjoyed and finished in a house. However, not everybody can afford their dreaming house. Most poor people in urban areas have to live in substandard housing. Although hundreds of experts have been sent and millions $US have been spent to solve this problem, however, housing problems in the Third World is still acute. In fact, part of Indonesia people specially some of urban Balinese should live in slum settlement. For some people, slum is perceived as a problem. However, from different perspective, slum can be regarded as a solution especially for the marginal groups in urban areas. What is our opinion? What cause of slum? And what is appropriate solution to improve it?
Keywords: slum settlement, problem and solution